HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN SUMBER INFORMASI IBU DENGAN PEMBERIAN MAKANAN USIA 0-6 BULAN DI POSYANDU CILEDUG TANGERANG - Apriyanti, Apriyanti; Asrianti Utami, Tuti; Jhariah Hidayah, Ainum (NHM PRESS, 2024)
Background: Feeding aged 0-6 months should only be given with breast milk, but some mothers still have difficulty fulfilling breastfeeding so mothers add it with mixed feeding or formula. Mothers who have newborns with family support have good knowledge and can provide the best food for their babies. Purpose: This study aims to analyze the relationship between mother's knowledge, family support and information sources with feeding aged 0-6 months in Posyandu Ciledug Tangerang. Methods: Correlational descriptive research design with a cross-sectional approach. The research sample was mothers who had babies aged 7-24 months as many as 108 respondents. Results: There is a relationship between knowledge and family support with feeding aged 0-6 months at Posyandu Ciledug Tangerang (p-value 0.000 and p-value 0.002 (<0.05)) and there is no relationship between information sources and feeding aged 0-6 month for respondents at Posyandu Ciledug Tangerang p-value 0.522 (> 0.05). Conclusion: Knowledge and family support help mothers to provide the best food aged 0-6 months at Posyandu Posyandu Ciledug Tangerang. Suggestion: Health workers at Posyandu services should be able to provide health promotion to increase family knowledge and support regarding feeding aged 0-6 months to pregnant and lactating women.